Fault analysis using power system simulator for engineering (PSS/E) software / Farah Lylia Nordin - Nordin, Farah Lylia (2010)
This thesis present two types of fault analysis performed by using the Power System Simulator for Engineering (PSS/E) software. The objective is to determine the highest fault current for every type of fault condition. The types of unsymmetrical fault are line to-ground fault, line-to-line fault and double-line-to-ground fault. The three-phase fault can be classified under symmetrical fault. Fault analysis was performed by using the Solve and Report Network with Unbalances (SCMU) and Automatic Sequence Fault Calculation (ASCC) tools provided by Power System Simulator for Engineering (PSS/E) software. The SCMU was performed to obtain the results of three-phase fault, line-to ground fault and double-line-to-ground fault currents. Line-to-line fault current was obtained by using the ASCC procedure. A case study of 23 bus system is used for the analysis of fault in order to obtain the value of current based on the various types of fault.